Wayside Diagnostic of Running Gear in Subway Vehicles Maintenance (Current Problems in Rail Vehicles, 2021)
The introduction describes the advantages of wayside diagnostics of running railway vehicles, existing systems and the system developed within the project TAČR Wayside Diagnostics of Railway Vehicles Running Gear. The next section describes selecteddiagnosable disorders, the detection of which is problematic or impossible during a static inspection in the depot. In addition to the option of switching to predictive maintenance, the automatic diagnostic system also performs a safety function, as it makes it possible to detect sudden faults that occur during operation. The paper concludes with a vision of how to integrate wayside diagnostics into an existing vehicle maintenance system.
Keywords: wayside diagnostic; railway vehicle; vehicle mantenance